The Effect of Work Stress and Job Involvement on Job Satisfaction of Employees in the Emergency Department of Dr. Soedarso Regional General Hospital Pontianak - Halifah Halifah; Devi Yasmin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The increasing number of patient visits and limited resources in the Emergency Department of Dr. Soedarso Regional General Hospital, Pontianak, have the potential to create work pressure that affects employees’ work attitudes. This study aims to analyze the effect of work stress and job involvement on employee job satisfaction, both partially and simultaneously. The study employed a quantitative approach with an associative design. The population as well as the sample consisted of 53 Emergency Department employees determined using a total sampling technique. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression, correlation coefficient, coefficient of determination, and F-test and t-test at a significance level of 0.05. The results show that work stress has a negative and significant effect on job satisfaction, while job involvement has a positive and significant effect on job satisfaction. Simultaneously, both variables have a significant effect on job satisfaction, with a correlation coefficient (R) of 0.787 indicating a strong relationship. The coefficient of determination (R²) of 0.619 indicates that 61.9% of the variation in job satisfaction can be explained by work stress and job involvement, while the remaining 38.1% is influenced by other variables outside the research model. Theoretically, this study clarifies the role of psychological work conditions in shaping job satisfaction within high-pressure healthcare environments. Practically, the findings provide implications for hospital management to manage work stress and enhance job involvement in order to improve job satisfaction and maintain service quality in the emergency department.